Foundational and practical aspects of resource analysis second international workshop, FOPARA 2011, Madrid, Spain, May 19, 2011, revised selected papers - Eekelen, Marko; Shkaravska, Olha; Peña, Ricardo (Lecture Notes in Computer Science,, 2012)
This book constitutes the refereed post-proceedings of the Second International Workshop on Foundational and Practical Aspects of Resource Analysis, FOPARA 2011, held in Madrid, Spain, in May 2011. The 8 revised full papers were carefully reviewed and selected from the papers presented at the workshop and papers submitted following an open call for contributions after the workshop. The papers are organized in the following topical sections: implicit complexity, analysis and verfication of cost expressions, and worst case execution time analysis.